Shortage of psychotropic medications in community pharmacies in Saudi Arabia: Causes and solutions - Yazed Sulaiman Al-Ruthia; Wael Mansy; Mohammad Barasin; Yazeed Mohammad Ghawaa; Mohammed AlSultan; Mohammad A. Alsenaidy; Solaiman Alhawas; Sultan AlGhadeer (Elsevier, 2017)
Background: Patients with mental disorders, such as depression and anxiety, who seek medical care in private psychiatric clinics in Riyadh, Saudi Arabia, have recently expressed concerns to doctors about difficulty in filling psychotropic medications, such as Amitriptyline and Aripiprazole, at retail community pharmacies. Objectives: The aim of this study was to investigate whether there is a shortage of some commonly prescribed psychotropic medications in retail community pharmacies in Saudi Arabia, and if so, to explore the possible reasons behind the shortage of these medications. Methods: The availability of 28 commonly prescribed psychotropic medications was checked in multiple retail community pharmacies in 4 different regions of Saudi Arabia. Further, potential reasons behind the shortage of some psychotropic medications in retail community pharmacies were also explored. Results: Amitriptyline, Amoxapine, Aripiprazole, Bupropion, Buspirone, Duloxetine, Haloperidol, Hydroxyzine, Lithium, Prochlorperazine, Procyclidine, Promethazine, Thioridazine, Trazodone, and Trifluoperazine were unavailable in over half of the 248 community pharmacies surveyed. Four possible reasons behind the shortage of these medications were reported by 31 pharmacists working in different retail community pharmacies' purchasing departments, with a majority (58.06%) reporting the primary reason for a shortage of these medications that they are slow-moving items with low profit margins. Conclusions: The findings of this study should expedite the reform process in both the Ministry of Health and the Saudi Food and Drug Authority (SFDA) to publish and enforce an essential list of medications for retail community pharmacies, which should include the most commonly prescribed psychotropic medications.